Perancangan Aplikasi Tabungan Siswa TK Al-Hurriyah Berbasis Web - Patria, Muhammad; Bawafi, Imam; Rahayu, Adellya; Sihombing, Feny Hertati; Syahindra, Wandi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this study was to design a student savings application at TK al-Hurriyah. The problem that arises is that the savings data management system that is currently running is still being done manually, recording and storing data is written in a book, and the calculations are still being done with a calculator. Based on the findings that show that the lack of an existing system indicates a deficiency in the software section to help manage savings data. So it is necessary to have a separate system for student savings, namely a web-based student savings information system. This study uses the system requirements method and system modeling using UML (Unified Modeling Language) to describe visually, which is then implemented with the PHP programming language (Hypertext Preprocessor) with MySQL database as the database used. The benefits of this research are expected to facilitate the process of collecting data on savings of TK al Hurriyah students and storing savings data, so that the information you want to get later will run quickly and accurately.